Problem chronologii w nowszych pracach dotyczących Bolka V. Przebieg wypraw wojennych z początku lat 30. XV w. wraz z uzupełnieniami do itinerarium księcia opolskiego - Woźny, Maciej (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The article deals with a war expedition by Bolko V, appearing in the latest historical works, which is said to have taken place in 1432. In examining the letter, which serves as the basis for describing military campaigns conducted that year, the author points out that the publisher made a mistake in dating it. The mistake was noticed and corrected by the publisher himself, but some contemporary historians have overlooked it. This leads to an incorrect presentation of the battles taking place in Upper Silesia during the first half of the 1430s. The author, confronting the content of the letter with the so-called Strzelin fragment, points out that it must have been written in 1430 in accordance with the correction issued by the publisher of the source.
Keywords: Hussite Wars; Bolko V; Meristow